The projected degradation of subtropical coral assemblages by recurrent thermal stress. Issue 1 (9th October 2020) - Cant, James; Salguero‐Gómez, Roberto; Kim, Sun W.; Sims, Carrie A.; Sommer, Brigitte; Brooks, Maxime; Malcolm, Hamish A.; Pandolfi, John M.; Beger, Maria
Abstract: Subtropical coral assemblages are threatened by similar extreme thermal stress events to their tropical counterparts. Yet, the mid‐ and long‐term thermal stress responses of corals in subtropical environments remain largely unquantified, limiting our capacity to predict their future viability. The annual survival, growth and recruitment of 311 individual corals within the Solitary Islands Marine Park (Australia) was recorded over a 3‐year period (2016–2018), including the 2015/2016 thermal stress event. These data were used to parameterise integral projection models quantifying the effect of thermal stress within a subtropical coral assemblage. Stochastic simulations were also applied to evaluate the implications of recurrent thermal stress scenarios predicted by four different Representative Concentration Pathways. We report differential shifts in population growth rates ( λ ) among coral populations during both stress and non‐stress periods, confirming contrasting bleaching responses among taxa. However, even during non‐stress periods, the observed dynamics for all taxa were unable to maintain current community composition, highlighting the need for external recruitment sources to support the community structure. Across all coral taxa, projected stochastic growth rates ( λs ) were found to be lowest under higher emissions scenarios. Correspondingly, predicted increases in recurrent thermal stress regimes may accelerate the loss of coral coverage, species diversity and structural complexity within subtropical regions. We suggest that these trends are primarily due to the susceptibility of subtropical specialists and endemic species, such as Pocillopora aliciae, to thermal stress. Similarly, the viability of many tropical coral populations at higher latitudes is highly dependent on the persistence of up‐current tropical systems. As such, the inherent dynamics of subtropical coral populations appear unable to support their future persistence under unprecedented thermal disturbance scenarios. Abstract : Demographic approaches transcend purely correlative appraisals into the stress responses of coral communities enhancing assessments of their viability. The authors show that despite more robust taxa and cooler thermal regimes compared to tropical reefs, future recurrent thermal stress and a dependency on external recruitment will impede the viability of subtropical coral communities.